Radiometric Surveying in the Vicinity of Witwatersrand Gold Mines - Coetzee, H (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
Uranium is generally associated with the gold ores of the Witwatersrand, at times at concentrations which may be economically viable for extraction as a by-product to the gold. Uranium and its radiogenic progeny are therefore found in many of the residues and wastes produced in the mining and processing of Witwatersrand ores. The airborne radiometric method is capable of detecting these wastes and the downstream concentrations of radioactive material deposited by sediment transport and chemical precipitation processes. Although the airborne method can provide full coverage of the area surveyed and is sensitive to small variations in surface radioactivity, its use as a quantitative environmental assessment tool is limited by a number of factors such as elevated natural background, secular equilibrium and disequilibrium, geometric factors and the lack of depth penetration of the method. Nevertheless the airborne radiometric method can be utilized in the investigation of a range of environmental problems related to mining in the Witwatersrand Goldfields and can play a valuable role as a screening tool in environmental risk assessments.